Предмет: Алгебра,
автор: MrDark73
Выражение (a+2)^3-3(a+2)^2+3(a+2)-1 можно записать в виде
Ответы
Автор ответа:
0
(a+2)³-3(a+2)²+3(a+2)-1=
=a³+6a²+12a-3(a²+4a+4)+3a+6-1=
=a³+6a²+12a-3a²-12a-12+3a+5=
=a³+3a²+3a-7
((x+y)³=x³+3x²y+3xy²+y³)
=a³+6a²+12a-3(a²+4a+4)+3a+6-1=
=a³+6a²+12a-3a²-12a-12+3a+5=
=a³+3a²+3a-7
((x+y)³=x³+3x²y+3xy²+y³)
Автор ответа:
0
a^3+3*a^2*2+3*a*2^2+2^3=a^3+6a^2+12a+8-3*(a+2)^2+3*(a+2)-1=a^3+6a^2+12a+8-3*(a^2+4a+4)+3a+6-1=a^3+6a^2+12a+8-3a^2-12a-12+3a+6-1=a^3+3a^2+1+3a
Похожие вопросы
Предмет: Математика,
автор: yarkova1990
Предмет: История,
автор: yliaaasssss
Предмет: Математика,
автор: poli57527
Предмет: Математика,
автор: Аноним
Предмет: История,
автор: zazazazazaza880